1993
DOI: 10.1073/pnas.90.11.4966
|View full text |Cite
|
Sign up to set email alerts
|

Axonal sprouting and laminin appearance after destruction of glial sheaths.

Abstract: Laminin, a large extracellular matrix molecule, is associated with axonal outgrowth during development and regeneration of the nervous system in a variety of animals. In the leech central nervous system, laminin immunoreactivity appears after axon injury in advance of the regenerating axons. Although studies of vertebrate nervous system in culture have implicated glial and Schwann cells as possible sources, the cells that deposit laminin at sites crucial for regeneration in the living animal are not known. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…These microglial cells migrate to the cortex, where they are found in their ‘quiescent’ stage during adulthood. During development, activated microglia assume a supportive role in myelinogenesis and axonogenesis by stimulating the synthesis of myelin basic protein and the induction of laminin, an extracellular matrix molecule that enhances neurite outgrowth [12,13]. However, the presence of activated microglia in the white matter tracts during development may also increase the vulnerability of the fetal brain to diverse brain insults.…”
Section: Introductionmentioning
confidence: 99%
“…These microglial cells migrate to the cortex, where they are found in their ‘quiescent’ stage during adulthood. During development, activated microglia assume a supportive role in myelinogenesis and axonogenesis by stimulating the synthesis of myelin basic protein and the induction of laminin, an extracellular matrix molecule that enhances neurite outgrowth [12,13]. However, the presence of activated microglia in the white matter tracts during development may also increase the vulnerability of the fetal brain to diverse brain insults.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LN was not detected by our immunohistochemical assays in these inflammatory infiltrates, suggesting a more effective involvement of FN in the genesis of CNS inflammatory lesions during T. gondii infection. Concerning the origin of this FN, it is possible that nervous or mononuclear cells present in the inflammatory infiltrates could release ECM molecules in nervous tissue (25)(26)(27). Indeed, some studies have demonstrated that motor neurons, glial cells and astrocytes are able to secrete ECM molecules such as FN and LN when neuronal-glial interaction occurs and during the astrocyte proliferative response following injury (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia stimulation is generally considered to involve activation by 1) molecules released directly by a lesion; or 2) a signal propagating from the site of injury via other cells, such as a calcium wave carried by glia. Such activated microglia, when accumulated at a lesion, would be expected in mammals to release neurotrophins such as brain-derived neurotrophic factor (BDNF), neurotrophic factor (NTF), and NT3 (Batchelor et al, 1999) and in leeches perhaps laminin (Masuda-Nakagawa et al, 1993), all of which have been shown to enhance axon growth and neuron survival. In addition, in the rat it has been shown that damage to the lens causes macrophages to release proteins that promote regeneration of retinal ganglion cell axons (Leon et al, 2000;Yin et al, 2003Yin et al, , 2006.…”
Section: Are Microglia Harmful or Helpful To Cns Repair?mentioning
confidence: 99%